Benign esophageal schwannoma: a brief overview and our experience with this rare tumor - Moro, Kazuki (Surg Case Rep, 2017)
BACKGROUND: Benign esophageal tumors are uncommon, comprising approximately 2% of esophageal tumors. Esophageal schwannomas constitute an even rarer entity, with few cases reported in the literature. CASE PRESENTATION: We present a 66-year-old male who was referred for dysphagia. A computed tomography scan showed a well-demarcated, enhancing, and homogenous esophageal tumor measuring 50 mm. The tumor was hypermetabolic on positron emission tomography, and an endoscopic ultrasound-guided fine needle aspiration demonstrated the presence of benign spindle cells. We performed an uncomplicated, simple, tumor enucleation through a cervical approach. Histology revealed spindle-shaped cells in a fasciculated, disarrayed pattern. Immunohistochemistry demonstrated positive staining for S-100 protein and negative staining for KIT, CD34, desmin, and α-smooth muscle actin. These findings were consistent with a benign esophageal schwannoma. CONCLUSIONS: We report our experience with esophageal schwannoma, a rare but benign diagnosis of the esophagus.